Harm Experienced from the Heavy Drinking of Family and Friends in the General Population: A Comparative Study of Six Northern European Countries - Mats Ramstedt; Erica Sundin; Inger Synnøve Moan; Elisabet E. Storvoll; Ingunn Olea Lund; Kim Bloomfield; Ann Hope; Sveinbjörn Kristjánsson; Christoffer Tigerstedt (SAGE Publishing, 2015)
Background Epidemiological research on alcohol-related harm has long given priority to studies on harm to the drinker. A limitation with this perspective is that it neglects the harm drinking causes to people around the drinker, and thus, it fails to give a full picture of alcohol-related harm in society. Aim The aim was to compare the prevalence and correlates of experiencing harm from the heavy drinking by family and friends across the Nordic countries and Scotland and to discuss whether potential differences match levels of drinking, prevalence of binge drinking, and alcohol-related mortality. Data and Method Data from recent national general population surveys with similar questions on experiences of harms from the drinking of family and friends were collected from Sweden, Finland, Denmark, Norway, Iceland, and Scotland. Results National estimates of the overall population prevalence of harm from the drinking of family and friends ranged from 14% to 28% across these countries, with the highest prevalence in Finland, Iceland, and Norway and lower estimates for Denmark, Sweden, and Scotland. Across all countries, the prevalence of harm from heavy drinking by family and friends was significantly higher among women and young respondents. Conclusion This study revealed large differences in the prevalence of harm across the study countries, as well as by gender and age, but the differences do not match the variation in population drinking and other indicators of harm. The implications of the findings for future research are discussed.